Caractéristiques distinctives des institutions publiques rurales mettant en oeuvre des innovations sociales locales. Rapports de la Pologne - Zajda, Katarzyna (Sociology of rural worlds in Poland and France: field research and studies, 2024)
Despite the unabated interest of researchers and practitioners from around the world in social innovation, few analyses have been conducted on implementation of social innovation in rural areas. What is more, activity of public institutions in implementation of social innovation is rarely addressed. The article explores the problem of implementation of local social innovations by public institutions in Polish rural municipalities. The objective of the analysis is to identify the characteristics that distinguish public institutions that have experience in implementing local social innovations from those that do not. Among the analyzed features are: 1. collaboration with local non-governmental organizations, 2. collaboration and information exchange with non-governmental organizations operating outside the given rural municipality, 3. involvement of residents of the municipality in activities aimed at addressing their social problems. The results of quantitative research conducted on a random sample of Polish rural municipalities will be presented. 330 public institutions which are key to solving local social problems participated in the study. Local social innovations are defined as alternative practices that are undertaken at the municipal level in order to solve social problems affecting its residents. The obtained results are deepened by discussing examples of social innovations that have been implemented.